2011
DOI: 10.1590/s1414-81452011000100006
|View full text |Cite
|
Sign up to set email alerts
|

Vivendo entre o pesadelo e o despertar: o primeiro momento no enfrentamento da diálise peritoneal

Abstract: Este artigo é originado de uma dissertação de mestrado cujo objeto foi o significado do enfrentamento do cliente portador de doença renal crônica mediante o início da diálise peritoneal. Os sujeitos do estudo foram considerados na perspectiva do Interacionismo Simbólico, que valoriza o significado dos elementos do mundo como determinantes para a interação. Seguindo os procedimentos metodológicos da Teoria Fundamentada nos Dados foram instituídos os cinco elementos do paradigma de análise: Causas, Contexto, Fat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
4

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 3 publications
0
11
0
4
Order By: Relevance
“…A good general level of information regarding PD and its specific characteristics can represent a protective factor, contributing to a better quality of administration of the dialytic technique 5 .…”
Section: Discussion Of Datamentioning
confidence: 99%
See 1 more Smart Citation
“…A good general level of information regarding PD and its specific characteristics can represent a protective factor, contributing to a better quality of administration of the dialytic technique 5 .…”
Section: Discussion Of Datamentioning
confidence: 99%
“…Because it is a method which can be undertaken in the client's home, PD leads to a series of adaptations in the environment where the therapy will take place, as well as the involvement and active participation of family members and people close to the client who has CKD in the dialytic phase. For this same reason, it falls to the nurse to assess the residence (individual room and other parts of the building) of the client who intends to be included in the PD program 5 . Due to all the transformations that it provokes in the life of the client and her family members, one can observe that the start of PD is a critical time in an individual's existential trajectory.…”
Section: Introductionmentioning
confidence: 99%
“…Studies indicate that this training needs to be planned even in the outpatient phase of chronic kidney disease, which, according to them, contributes to the reduction of peritonitis, which is the greatest aggravation in this therapy. 10,11 Among the actions that precede the training activities of the user and the family, it is ideal for the nurse to construct a script that contemplates the clinical, social, psychological and spiritual aspects of the user, their family relations, the socioeconomic and housing conditions, which assist in the collection of information to know the difficulties and potentialities resulting from this treatment. 8 In this sense, the importance of the theoretical details of the training promoted by the nurse to the user or family caregiver, with use of explanatory materials, activities, and returns to evaluate the correct technique performed by the family member or user.…”
Section: The Nurse's Actions Towards the Training Of The Family Membementioning
confidence: 99%
“…Following the same logic, different studies emphasize the need for nurses to perform an assessment of the user's capacity for self-care, to identify housing conditions through home visits and the formulation of a script, as well as a family analysis with aspects of interaction, integrity and coping, given that the family relations evaluated therein have an impact on the achievement and efficacy of therapy. 8,11,13 It emphasizes that during the training period, the nurse develops actions such as the user's approach to the renal replacement therapy service through a guided visit to the unit, the evaluation of the cognitive abilities of the chronic renal patient or its family member,the offer of training in order to perform home therapy and simulation of intercurrences, follow up of the user to the surgical center for the implantation of the abdominal catheter, and periodic home visits for follow up of the patient. 8,11 By using this line of thought, it is important to remember that in addition to carrying out educational assistance actions, to be observed at home, nurses need to provide a humane welcoming.…”
Section: The Nurse's Actions Towards the Training Of The Family Membementioning
confidence: 99%
“…Accordingly, it was observed that the patients are unaware of the reasons of CRF; consequently they realize it only when the symptoms are already advanced, since its development and chronicity occur in a silent way. For Santos and Valadares (2011) this ignorance associated with the disease and its treatment leaves room for arising ideas sometimes more perverse than the reality itself, overwhelming the subject and leaving him unsafe, so the event was mythologized causing frightening and desperate figures.…”
Section: Figure1: Correspondence Factor Plan Of Social Representationmentioning
confidence: 99%